2021
DOI: 10.1021/acs.jpcc.1c00391
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Insight into the Hydrodeoxygenation of Hydroquinone over Au/a-TiO2 Catalyst

Abstract: The mechanism and kinetic features of hydrodeoxygenation of hydroquinone over the oxygen-defective anatase (a-TiO 2 ) supported gold (Au) catalyst were studied by density functional theory calculations. The investigation of reaction pathways and energetics identified that the conversion of hydroquinone over Au 10 /a-TiO 2 (001) went through several key reaction intermediates including benzoquinone, 1,4-cyclohexanediol, and cyclohexanol. The dehydrogenation of hydroquinone to benzoquinone intermediate occurred … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 76 publications
0
6
0
Order By: Relevance
“…Combination of metal and reducible metal oxide (as support or promoter) has been generally shown higher DDO activity compared with bare metal on an inert support. [14,48] However, only few studies investigated the effect of SMSI degree on the DDO activity/selectivity. In this section, we analyze the approaches of tuning degree of SMSI and their consequences on the activity and selectivity for HDO of phenolics, with particular focus on DDO toward aromatics.…”
Section: Tuning Smsi To Enhance Ddo Of Phenolicsmentioning
confidence: 99%
“…Combination of metal and reducible metal oxide (as support or promoter) has been generally shown higher DDO activity compared with bare metal on an inert support. [14,48] However, only few studies investigated the effect of SMSI degree on the DDO activity/selectivity. In this section, we analyze the approaches of tuning degree of SMSI and their consequences on the activity and selectivity for HDO of phenolics, with particular focus on DDO toward aromatics.…”
Section: Tuning Smsi To Enhance Ddo Of Phenolicsmentioning
confidence: 99%
“…The red numbers represent activation barriers (eV), while the blue numbers are reaction energies (eV). 191 the possibility of generating a transient superoxo state of O 2 as a reaction intermediate. Actually, with a combination of experimental and theoretical research, Adachi et al 196 have shown that the charge on the oxygen species can be tuned by kelvin probe force spectroscopy (KPFS) charge manipulation in a systematic manner from 4e to 2e 2À ).…”
Section: O 2 and H 2 Omentioning
confidence: 99%
“…Conversion of hydroquinone through different pathways. The red numbers represent activation barriers (eV), while the blue numbers are reaction energies (eV) 191 …”
Section: The Adsorption Activation and Reaction Of Small Inorganic Mo...mentioning
confidence: 99%
See 1 more Smart Citation
“…CO oxidation on RuO 2 (110) surfaces, 85 Pt nanocatalysts, 86 Cu/Rh bimetallic catalysts, 87 Ag clusters, 88 and Ru/RuO 2 interfaces 89 is discussed. Theoretical studies on other important reactions are also included: the HER on the VS 2 monolayer 90 or black phosphorus, 91 the electrochemical CO 2 reduction reaction on h-BN nanosheets, 92 photocatalytic CO 2 reduction on silver nanoclusters, 93 CO 2 dissociation on Cu clusters, 94 the methanol-to-olefins (MTO) process on different zeolites, 95 the ORR on the two-dimensional NiTe monolayer, 96 the nitrogen reduction reaction on Ru-or Fe-supported Nb 2 C MXene, 97 NO reduction by CO on Cu 2 O(110) and Pd 1 / Cu 2 O(110), 98 NO oxidation on different oxides, 99 methane steam reforming on Ni, Pt, and Pd, 100 dry reforming of methane on the Ni/Mo alloy, 101 the B 2 O 3 -catalyzed oxidative dehydrogenation of propane, 102 the hydrodeoxygenation of hydroquinone on Au/TiO 2 , 103 the hydrogenation of CO 2 to methanol over Pt 4 /In 2 O 3 , 104 syngas conversion to ketene on ZnCr 2 O 4 , 105 the structural and optoelectronic properties of ZnSe 1−x Te x photocatalysts, 106 bimetallic salen-complex-catalyzed epoxide hydration, 107 Rh-catalyzed formaldehyde hydroformylation, 108 the peroxidase and oxidase-like properties of nanoceria in biosystems, 109 the formation of polarons in TiO 2 , HfO 2 , and BiVO 4 , 110,111 and interfacial charge transfer in Li− O 2 batteries. 112 This VSI reflects the recent progress in the experimental and theoretical development of chemical energy in mainland China.…”
mentioning
confidence: 99%